2015
DOI: 10.1155/2015/797606
|View full text |Cite
|
Sign up to set email alerts
|

Photodegradation of Eosin Y Using Silver-Doped Magnetic Nanoparticles

Abstract: The purification of industrial wastewater from dyes is becoming increasingly important since they are toxic or carcinogenic to human beings. Nanomaterials have been receiving significant attention due to their unique physical and chemical properties compared with their larger-size counterparts. The aim of the present investigation was to fabricate magnetic nanoparticles (MNPs) using a coprecipitation method, followed by coating with silver (Ag) in order to enhance the photocatalytic activity of the MNPs by loa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(8 citation statements)
references
References 74 publications
0
8
0
Order By: Relevance
“…In five-minute intervals, an aliquot (2 mL) was taken out in a glass cuvette to be measured in the UV-vis spectrophotometer in order to record the dye degradation absorbance. The advantage of employing the UV light was to produce the electron and hole pair (e−/h+) with a high energy state which migrated to the CuO/PET nanocomposite surface to initiate a wide range of chemical reactions [36]. During a five-minute interval, the blue color intensity of the MB dye solution gradually disappeared and the solution became colorless with the UV light continuously irradiating.…”
Section: Photodegradation Study Of Mb Dyementioning
confidence: 99%
“…In five-minute intervals, an aliquot (2 mL) was taken out in a glass cuvette to be measured in the UV-vis spectrophotometer in order to record the dye degradation absorbance. The advantage of employing the UV light was to produce the electron and hole pair (e−/h+) with a high energy state which migrated to the CuO/PET nanocomposite surface to initiate a wide range of chemical reactions [36]. During a five-minute interval, the blue color intensity of the MB dye solution gradually disappeared and the solution became colorless with the UV light continuously irradiating.…”
Section: Photodegradation Study Of Mb Dyementioning
confidence: 99%
“…Besides, it was observed that the highest absorption corresponding to MB weakened by increasing the irradiation time when prepared membranes for different time intervals are used, prior to final disappearance, indicating that MB degradation was accomplished and no other UV-Vis spectroscopy detectable products were left in the reaction mixture. The reason for this is the start of depredation of the poly aromatic rings in the dye, which resulted in the formation of mono-substituted aromatics 41,42 . These results are confirmation of the fact of photocatalytic process having the ability of converting toxic chemicals to non-toxic chemicals, and thus this method is considered promising in the elimination of MB from the environment.…”
Section: Photodegradation Of Dye Photodegradation Of Cationic Dye (Mb)mentioning
confidence: 99%
“…It was further observed that there was reduction in the absorption peak corresponding to FG by increase in the irradiation time when membranes were used in the form of photocatalyst, prior to final disappearance that indicated the accomplishment of FG degradation without UV-Vis spectroscopy detecting any other product left in the reaction mixture. The start of degradation of the poly aromatic rings in the dye resulting in the formation of monosubstituted aromatics was the reason for this 41,42 . This result is confirmation of the ability of the photo catalytic process in converting toxic chemicals to non-toxic chemicals, and therefore this procedure is seen as promising in the elimination of Fast green.…”
Section: Photodegradation Of Anionic Dye (Fast Green)mentioning
confidence: 99%
“…High-resolution atomic force microscopy (AFM) was used to test morphological features and to produce a topological map (Veeco-di Innova Model-2009-AFM-USA). nanoparticles (MNPs) were prepared as described in our previous work [20]. MNPs were obtained by dissolving 3.3 g of FeSO 4 •7H 2 O and 2 g of NaNO 3 in 50 mL of distilled water.…”
Section: Instrumentationmentioning
confidence: 99%
“…Scheme 1 presents the schematic route for fabrication of the core-shell nanospheres. The first step was the fabrication of the magnetic Fe 3 O 4 nanoparticles prepared using our previous work [20] through the chemical precipitation method. The preparation of the magnetic Fe 3 O 4 nanoparticles was performed by mixing FeSO 4 •7H 2 O with NaNO 3 in purified water, followed by the addition of NaOH solution for the precipitation of the Fe 3 O 4 nanoparticles (black powder).…”
Section: Characterisation Of the Core-shell Fe 3 O 4 /Sio 2 /Tio 2 Namentioning
confidence: 99%